A smorga: From the novel to the cinema - Puíme Sabugueiro, Montserrat (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The novel by Eduardo Blanco Amor written in Galician language A smorga is compared in this paper to the films Parranda by Gonzalo Suárez and A smorga by Ignacio Vilar. Interartistic  methodology is arranged here due to the possibility from Comparative Literature which allows the study of different artistic assessments in this case literature and cinema. In such a way, it is analysed space-time, the teller, characters, movies critics, and so on. The findings reveal remarkable differences between cinema and literature in this works. It is concluded also that the base text of the novel is preserved in some way.